Flying in the canopy: taxonomic and ecological analysis with geometric morphometrics and distributional notes on Athis delecta and Athis jaliscana (Lepidoptera: Castniidae) - García-Díaz, José De Jesús; Ramírez-Ponce, Andrés; López-Godínez, Bernardo; Torres-Yañez, Elier (Zootaxa, 2025)
Athis Hübner, [1819] is the most diverse genus of diurnal moths of the family Castniidae distributed in America. Little is known about the biology and distribution of most species. Based on an exhaustive review of entomological collections and field work, we provide information on the ecology, behavior, distribution and variability of two rare and little-known species: A. delecta (Schaus, 1911) and A. jaliscana López-Godínez & Porion, 2012. We also illustrate for the first time the wing venation and male genitalia for both species. Athis delecta is reported for the first time in the Mexican state of Puebla. Findings in the field suggest that these two species have an atypical average flight height for Castniidae, being recorded between four and ten meters above the ground. Furthermore, since previous comparisons between Athis delecta and A. jaliscana were based solely on wing pattern, we conducted a geometric morphometric analysis to evaluate and illustrate potential differences in wing shape between males of both species. The present work expands the knowledge about the biology of the family and demonstrates that geometric morphometrics is an appropriate tool for future taxonomic studies of Castniidae.